The effects of seed pretreatment on seed germination and biochar soil mixture on early survival of seedlings of Faidherbia albida (Del) Chev in nursery - Kedir, Miftah; Weldeyohannes, Abrhame; Cherinet, Abirham; Tadesse, Chala (Journal of Agriculture and Environment for International Development (JAEID), 2025)
Appropriate pretreatment of seed and soil mixture of nursery are required for proper seed germination and seedlings growth, respectively. Faidherbia albida (Del) Chev (syn. Acacia albida [Del.]) is a useful tree species that improve soil fertility, and supply dry season livestock fodder in some climatic zones of Africa. However, it is difficult to grow F. albida in clay soils and methods to improve the cultivation conditions are highly required. Although biochar can be a potential ingredient of nursery soil mixture in deforested areas, information is lacking about its effect in clay soil nursery sites. Seeds of F. albida are also difficult to germinate in a short period of time. Accordingly, this study was conducted to determine the effects of nicking, and warm and cold water stratification seed pretreatments on improving the seeds germination. Then different proportional ratios of bio-chars of saw dust, chat (Catha edulis Forsk) leaves and coffee (Coffea arabica L.) husks pyrolysed at 300 and 350°C temperature were mixed with local soil, and compost to grow transplanted seedlings in the first year of eight months and then continued to second year totally 20 months old. Among the presowing seed treatment, stratification resulted in greatest number of germination of the seeds, about 76%. The effect of the soil mixtures on the root collar diameter (RCD) growth was greater than the corresponding stem height growth. The greatest RCD and height growth was obtained from local soil, about 0.84cm, and 28cm, respectively. The minimum growth of RCD was obtained in soil mixtures of local soil, compost and biochar of sawdust 350°C. However, 25% biochar of saw dust 300°C showed maximum RCD growth in eight months. In the first year, although, the soil mixture that contained only local soil was the best in increasing the growth of RCD and height of seedlings, it was the least in the number of seedlings survived. In 20months, the highest survival about 94%, root collar diameter of 0.88cm and height of 30.85cm was obtained from the mixture of local soil and biochar of sawdust 300°C in the ratio of 03:01, while the least survival and growth was obtained from unmixed local soil. Soil mixtures that contained biochar in all cases improved the survival of seedlings. Therefore, seedling growing in clay loam soils should include biochar pyrolysed at appropriate temperature for better survival of seedlings of F. albida.